Evaluation of Nutritional Content and Antioxidant Activity of Purple Sweet Potato Pudding Enriched with Red Dragon Fruit - St. Ika Fitrasyah; Sukmawati Sukmawati; Ariani Ariani; Abdul Fandir (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Degenerative diseases remain a leading cause of mortality worldwide, including in Indonesia. Unhealthy dietary patterns are among the major modifiable risk factors, highlighting the importance of developing nutritious functional foods. This study aimed to analyze the nutritional composition, antioxidant activity, acceptability, and serving size of purple sweet potato pudding enriched with red dragon fruit as a potential functional snack. This descriptive observational study was conducted through laboratory analyses and sensory evaluation. Protein content was determined using the UV–Vis spectrophotometric method, fat content using Soxhlet extraction, carbohydrate content using the anthrone method, and antioxidant activity using the DPPH assay. Acceptability was evaluated through a hedonic test. Data were analyzed using One-Way ANOVA. The results showed that the best formulation was P3, consisting of 37.5% purple sweet potato and 62.5% red dragon fruit. This formulation showed the highest acceptability in terms of color and taste. The nutritional composition of P3 per 100 g included 65.1 kcal energy, 3.9 g protein, 0.3 g fat, 11.7 g carbohydrates, and 3.7 g fiber, with an antioxidant capacity of 67.3 mg. A 100 g serving contributed 3% of the recommended dietary allowance (RDA) for energy, 4% for protein and carbohydrates, and 12% for fiber. These findings indicate that purple sweet potato pudding enriched with red dragon fruit has potential as a functional snack with antioxidant properties that may support degenerative disease prevention